P0681 Real-world efficacy of 15-mg upadacitinib for induction therapy in patients with mild-to-moderate Ulcerative Colitis - S He; Y Tian (Journal of Crohn’s and Colitis, 2026)
Abstract Background Clinical trials have established upadacitinib 45 mg for induction of remission in moderate-to-severe ulcerative colitis (UC). We report the real-world experience with upadacitinib at a single center, focusing on its use in patients with mild to moderately active disease who were treated with a 15 mg dose. Methods A single-center, prospective cohort study was conducted, including patients who started upadacitinib treatment between May 2023 and December 2024. Treatment outcomes were assessed using clinical, endoscopic, histological, and laboratory parameters. Adverse events were documented. Results Fifty patients with active UC were enrolled. The study population comprised patients with mildly (42%) and moderately (58%) active disease. Most patients (94%, 47/50) were bio-naïve. At week 4, the clinical response rate was 84%. At week 12, the clinical response rate was 84%, with 73.7% (28/38) achieving clinical remission and 50.0% (19/38) achieving endoscopic remission. The mucosal healing rate was 37.8% (14/37). The most frequent adverse events were respiratory tract infection (24.0%, 12/50), hypercholesterolemia (26.0%, 13/50), and acne (14.0%, 7/50). Herpes zoster was reported in one patient (2.0%), and one patient (2.0%) discontinued treatment due to an adverse event. Conclusion This real-world study demonstrates the rapid efficacy and acceptable safety profile of upadacitinib 15 mg in bio-naïve patients with mild-to-moderate ulcerative colitis. References: 1. Danese S, Vermeire S, Zhou W, Pangan AL, Siffledeen J, Greenbloom S, et al. Upadacitinib as induction and maintenance therapy for moderately to severely active ulcerative colitis: results from three phase 3, multicentre, double-blind, randomised trials. Lancet 2022; 399 (10341): 2113-2128. doi: 10.1016/s0140-6736(22)00581-5. 2. Nogami A, Asonuma K, Okabayashi S, Ikenouchi M, Matsuda T, Shinzaki S, et al. Real-World Comparative Effectiveness and Safety of Filgotinib and Upadacitinib for Ulcerative Colitis: A Multicentre Cohort Study. United European Gastroenterology Journal 2024; 12 (10): 1357-1366. doi: https://doi.org/10.1002/ueg2.12704. 3. Boneschansker L, Ananthakrishnan AN. Comparative Effectiveness of Upadacitinib and Tofacitinib in Inducing Remission in Ulcerative Colitis: Real-World Data. Clin Gastroenterol Hepatol 2023; 21 (9): 2427-2429.e2421. doi: 10.1016/j.cgh.2023.03.040. 4. Wu H, Xie T, Yu Q, Su T, Zhang M, Wu L, et al. An Analysis of the Effectiveness and Safety of Upadacitinib in the Treatment of Inflammatory Bowel Disease: A Multicenter Real-World Study. Biomedicines 2025; 13 (1): 190. doi: 10.3390/biomedicines13010190. 5. Gilmore R, Fernandes R, Hartley I, Arzivian A, Leong R, Andrew B, et al. Upadacitinib induction is effective and safe in ulcerative colitis patients including those with prior exposure to tofacitinib: a multicenter real-world cohort study. Intest Res 2024; 0 doi: 10.5217/ir.2024.00127. 6. Parmentier JM, Voss J, Graff C, Schwartz A, Argiriadi M, Friedman M, et al. In vitro and in vivo characterization of the JAK1 selectivity of upadacitinib (ABT-494). BMC rheumatology 2018; 2 23. doi: 10.1186/s41927-018-0031-x. 7. Sandborn WJ, Ghosh S, Panes J, Schreiber S, D’Haens G, Tanida S, et al. Efficacy of Upadacitinib in a Randomized Trial of Patients With Active Ulcerative Colitis. Gastroenterology 2020; 158 (8): 2139-2149.e2114. doi: 10.1053/j.gastro.2020.02.030. 8. Friedberg S, Choi D, Hunold T, Choi NK, Garcia NM, Picker EA, et al. Upadacitinib Is Effective and Safe in Both Ulcerative Colitis and Crohn’s Disease: Prospective Real-World Experience. Clin Gastroenterol Hepatol 2023; 21 (7): 1913-1923.e1912. doi: 10.1016/j.cgh.2023.03.001. 9. Traboulsi C, Ayoub F, Silfen A, Rodriguez TG, Rubin DT. Upadacitinib Is Safe and Effective for Crohn’s Disease: Real-World Data from a Tertiary Center. Dig Dis Sci 2023; 68 (2): 385-388. doi: 10.1007/s10620-022-07582-w. Conflict of interest: Mr. He, Shengduo: Grants: No grants have been received from any organization or entity related to this work. Personal Fees: No personal fees (e.g., honoraria, speaker fees) have been received from any relevant organization. Consulting: No consulting agreements or services have been provided to any entity related to this work. Support for travel for meetings to support study: No travel support for meetings related to this study has been received. Shareholder: No ownership interest (including stocks, shares, or equity) in any company whose products or services are discussed in this manuscript. Fees for participation in review activities: No fees have been received for participating in review activities (e.g., data monitoring boards, endpoint committees) related to this work. Payment for writing or reviewing the manuscript: No payment has been received for writing or reviewing this manuscript from any third party. Non-financial support: No non-financial support (e.g., equipment, materials) has been provided by external entities for this study. Provision of writing assistance, medicines, equipment, or administrative support: No writing assistance, medicines, equipment, or administrative support has been provided by external parties for this work. Other: No other potential conflicts of interest exist. Tian, Yu: Grants: No grants have been received from any organization or entity related to this work. Personal Fees: No personal fees (e.g., honoraria, speaker fees) have been received from any relevant organization. Consulting: No consulting agreements or services have been provided to any entity related to this work. Support for travel for meetings to support study: No travel support for meetings related to this study has been received. Shareholder: No ownership interest (including stocks, shares, or equity) in any company whose products or services are discussed in this manuscript. Fees for participation in review activities: No fees have been received for participating in review activities (e.g., data monitoring boards, endpoint committees) related to this work. Payment for writing or reviewing the manuscript: No payment has been received for writing or reviewing this manuscript from any third party. Non-financial support: No non-financial support (e.g., equipment, materials) has been provided by external entities for this study. Provision of writing assistance, medicines, equipment, or administrative support: No writing assistance, medicines, equipment, or administrative support has been provided by external parties for this work. Other: No other potential conflicts of interest exist.